Major Complications in FESS: Tips from Expert Surgeons. (23rd August 2013) - Tewfik, Marc A.; Wormald, Peter J.; Valentine, Rowan; Carrau, Ricardo; Hwang, Peter H.; Stamm, Aldo E. C.
Abstract : Program Description: Identify high‐risk situations pre‐operatively in patients undergoing FESS. Educational Objectives: 1) Identify high‐risk situations pre‐operatively in patients undergoing FESS. 2) Apply intra‐operative measures and technical pearls in order to avoid serious complications during FESS. 3) Articulate a clear plan for the management of intraoperative emergencies, including orbital hematoma and internal carotid artery injury.